Identification and synthesis of metabolites of the new 4.5-dihydroisoxazol-5-carboxamide derivate Authors - Alexander L. Khokhlov; Ilya I. Yaichkov; Mikhail A. Alexeev; Mikhail K. Korsakov; Anton A. Shetnev; Sergey A. Ivanovsky; Nikita N. Volkhin; Sergey S. Petukhov; Elena A. Vasilyeva (Belgorod National Research University, 2024)
Introduction: 3-(2-butyl-5-chloro-1H-imidazole-4-yl)-N-[4-methoxy-3-(trifluoromethyl)phenyl]-4,5-dihydro-1,2-oxazole-5-carboxamide is new antirheumatic drug. It is necessary to identify and synthesize the biotransformation products for its complete pharmacokinetic study. Materials and Methods: A biotransformation study was carried out by intraperitoneal administration of the drug to Wistar rats and Soviet Chinchilla breed rabbits. Animal blood sampling was performed before the injection and 0.5 h, 1 h, 2 h, 4 h, 24 h after the injection of the investigated compound. The samples were immediately centrifuged for plasma separation. Urine was simultaneously collected from rats before the administration and at intervals of 0-2 h, 2-4 h, 4-6 h, 6-24 h after administration, faeces - before administration and at intervals of 0-12 h and 12-24 h after administration. The samples were analyzed by HPLC-MS/MS after immediate preparation by adding acetonitrile. Results and Discussion: 3-(2-butyl-5-chloro-1H-imidazole-4-yl)-4,5-dihydro-1,2-oxazole-5-carboxylic acid and 4-methoxy-3-(trifluoromethyl)aniline - hydrolysis products of the active substance were found during the analysis of plasma, urine and fecal samples. The 4,5-dihydro-1,2-oxazole-5-carboxylic acid derivative has been synthesized. The second metabolite is a raw material for production of active pharmaceutical substance. During comparative tests, no significant difference between the retention times, ratio areas of chromatographic peaks at the main MRM-transitions and mass spectra of these metabolites on chromatograms of standard and animal samples was found, which indicates the correct identification of biotransformation products. Conclusion: The studied drug undergoes biotransformation by hydrolysis to form two main metabolites: 3-(2-butyl-5-chloro-1H-imidazole-4-yl)-4,5-dihydro-1,2-oxazole-5-carboxylic acid and 4-methoxy-3-(trifluoromethyl)aniline. The structure of the metabolites was confirmed by comparison with the synthesized standard samples using HPLC-MS/MS.